Intrinsic Hormone-Like Molecules and External Root Resorption During Orthodontic Tooth Movement. A Systematic Review and Meta-Analysis in Preclinical in-Vivo Research - Spoerri, Andreas; Koletsi, Despina; Eliades, Theodore (Frontiers in Physiology, 2018)
Background External root resorption constitutes an adverse effect of orthodontic treatment. The aim of the present systematic review was to provide a synthesis of animal studies based on experimental data on the effect of induced intrinsic/ hormone-like substance administration on external root resorption after orthodontic tooth movement. Methods An electronic database search of the literature was performed (Medline via PubMed, EMBASE, LILACS and Open Grey). Search terms included root resorption, tooth movement and animal type, while data was extracted in standardized piloted forms. Risk of bias assessment was made using the SYstematic Review Centre for Laboratory animal Experimentation (SYRCLE) guidelines for animal studies and reporting quality was assessed through ARRIVE (Animal Research: Reporting In Vivo Experiments). Random effects meta-analysis was performed for the outcome root resorption after orthodontic tooth movement. Results Of the 124 articles initially retrieved, 13 were eligible for inclusion in the systematic review, while only 2 were included in the quantitative synthesis. In 11 studies rats were used as experimental units, whereas two were performed on mice. Five studies investigated the effect of Prostaglandin E2, four studies the effect of Thyroxine, two the effect of Calcium, while the rest investigated Misoprostol, Interleukin-12 and Interleukin-4. Risk of Bias in all studies was judged to be high overall, while reporting quality was suboptimal. According to the quantitative synthesis, there was no difference in root resorption after orthodontic tooth movement when Prostaglandin E2 coupled with Calcium was administered in comparison to no substance administration (SMD: 0.48mm2; 95%CI: -0.22, 1.19; p= 0.18). Conclusions Overall, there was no evidence to suggest a variation in root resorption when Prostaglandin E2 and Calcium were administered, while there is an overriding need for further high quality experimental studies to inform available evidence on the effect of intrinsic substances on external root resorption.